A Measurable SocialToTech Software Trust Framework. (February 2019) - Yang, Xi; Luo, Ping; Jabeen, Gul
Abstract: With the rapid development of Internet, software trustworthiness has been increasingly important. How to measure this property has become a real challenge. Based on Sociology Trust system, this paper presents a framework which could be measurable, called as SocialToTech Software Trust Framework (SSTF). The SSTF includes three parts of software trustworthiness and this paper proposes a whole metric solution through a generalized indicator Cost-Loss.